Strengthening the Equity in Athletics Disclosure Act to Improve Gender Equity Transparency & Institutional Accountability in the Future - Ellen Staurowsky (University of Kansas Libraries, 2023)
In 1994, the United States Congress enacted The Equity in Athletics Disclosure Act (EADA). The EADA requires colleges and universities receiving federal financial assistance to provide an annual public report on the number of athletic participation opportunities provided to men and women athletes at the varsity level and the allocation of resources and personnel made in support of those opportunities.  The passage of the EADA occurred on the heels of the 20th anniversary of Title IX of the Education Amendments Act, a time marked by the realization that the vast majority of schools around the country were not in compliance with Title IX's requirements as applied to athletic departments two decades after its passage (NCAA Staff, 1993). The purpose of the EADA when initially proposed in 1993 was to provide accessible information to stakeholders, most specifically prospective students, the public, and the U.S. Congress, that would allow interested parties to raise questions regarding the fair and equitable treatment of women athletes in the nation's intercollegiate athletic programs. The annual report, colloquially referred to as the EADA report, is officially called The Report on Athletic Program Participation Rates and Financial Support Data. Three decades after the passage of the EADA and five decades after the passage of Title IX, there is reason to question whether the EADA has served its purpose.  During Title IX's 50th anniversary year, researchers and journalists uniformly reported a systemic failure to comply with Title IX in the area of athletics (Staurowsky et al., 2022; USA Today Staff, 2022; Wilson, 2022). Over the years, some have argued that the EADA should be eliminated (Keen, 2007), others have documented how valuable the information from the EADA is to researchers, journalists, and litigators (Tatos, 2019); others have recommended changes that would strengthen the data collection required under the EADA (Staurowsky et al, 2022); and others have argued that something akin to an EADA requirement needs to be adopted nationwide to help address sweeping gender inequities in athletics at the high school level (Green, 2008). This essay begins with an overview of the current state of Title IX compliance and gender equity in college sport, revisits the history of the EADA, provides an overview of what the EADA covers and who uses it, explores the criticisms and limitations of the EADA, and concludes with recommendations for making the EADA a more effective tool.